Manejo de la paja toquilla Carludovica palmata Ruiz & Pav. en comunidades de Santa Elena, Costa de Ecuador - Palacios, Walter (2016)
An investigation into the handling of the toquilla straw Carludovica palmata, of the Cyclanthaceae family is presented. The study was conducted in three districts of the Province of Santa Elena, Coast and workshops with community representatives regarding the cultivation and management of the plant is up, and the - la straw) obtained from the leaves.